Study on the influence of periodic roof fracturing on the mechanical disturbance characteristics of coal and gas outburst behavior in the mining face - Chunhua Zhang; Ziyue Chen; Xin Wu; Jingyu Ma; Jinquan Chen (PLoS ONE, 2026)
To elucidate the stress evolution characteristics of coal and the gas-dynamic response mechanism during periodic roof fracturing in longwall mining, the 3DEC numerical simulation software was employed to investigate the distribution characteristics of the abutment pressure at the instant of roof fracturing and elastic rebound. Based on the coupling relationship between abutment pressure and gas pressure, the gas occurrence characteristics in the mining face were further analyzed. The results indicate that, with increasing mining advance, the stress distribution after roof fracturing—affected by the roof suspension length and elastic rebound behavior—differs significantly from conventional patterns. As the mining face advances, the length of the overlying hard roof increases, and the elastic rebound behavior at the moment of roof failure reduces the vertical stress on the coal seam, thereby forming a stress-relief zone (Zone II) ahead of the working face. Using the COMSOL Multiphysics software for simulation, it was concluded that the elastic rebound at the moment of roof failure, in conjunction with the cyclic pressurization process, jointly determines the timing characteristics of coal energy release, which has a direct dynamic control effect on the initiation and eruption of gas outbursts. The stress perturbations caused by roof elastic rebound not only alter the mechanical structure and fracture evolution of the coal body, but also influence the occurrence and flow state of gas, thereby controlling the conditions and dynamic intensity of coal and gas outbursts. It provides a new theoretical basis for the prevention and control of gas outbursts and roof-related disasters.